Inequality and migration: reflections on the effects of the pandemic in Latin America (Revista Científica Integrada, 2024)
Objective: This essay aims to reflect the relationship between inequality, migration and the impacts of the Covid-19 pandemic in Latin America. Results: The study adopted a methodology based on bibliographic review and secondary data analysis. The methodology involves the analysis of scientific studies, reports from international organizations and relevant statistical data. Highlighting measures adopted to contain the spread of Covid-19, which generated disproportionate effects on the most vulnerable groups, resulting in significant impacts on the economy and access to basic services. This has further affected the migration crisis, as migrants face additional difficulties without access to social protection policies in relation to access to jobs. In this context, international cooperation plays an important role in facing global challenges related to migration and inequality in Latin America, in which joint actions between countries and international support are essential to face this problem and promote more equitable development in Latin America region.
Keywords: Inequality; Migration; Latin America; Pandemic; COVID-19